Effect of Elevated Atmospheric CO2 and Temperature Increases on the Severity of Basil Downy Mildew Caused by Peronospora belbahrii Under Phytotron Conditions. Issue 2 (20th August 2015) - Gilardi, Giovanna; Pugliese, Massimo; Chitarra, Walter; Ramon, Ivano; Gullino, Maria Lodovica; Garibaldi, Angelo
Abstract: Three experimental trials have been carried out on the basil (Ocimum basilicum)– downy mildew (Peronospora belbahrii ) pathosystem, under phytotron conditions, to evaluate the effect of simulated elevated atmospheric CO2 concentrations and temperatures as well as that of their interaction. Six CO2 and temperature combinations were tested to establish their effect on disease development. The photosynthetic efficiency (PI) and chlorophyll content index (CCI) of the basil plants were monitored throughout the trials. Average disease incidence was 43.8% under standard conditions (18–22°C and 400–450 ppm of CO2 ), while average disease severity was 22.1%. In the same temperature regime, a doubled level of CO2 caused a significant increase in both disease incidence and severity. When temperatures ranged between 18 and 26°C, CO2 at 800–850 ppm increased disease incidence. At the highest temperatures tested, that is at 26–30°C, which are not favourable for downy mildew development, the increase in CO2 had no significant effect on disease incidence. A decreasing trend of PI was observed for the PI values of the inoculated plants. This trend was particularly pronounced for high CO2 levels at the end of the experiment. In the same way as for disease development, lower values were recorded for the inoculated plants at the end of the experiment at 18–22°C for both CO2 concentrations and at 22–26°C for 850 ppm of CO2 . The non‐inoculated plants showed higher photosynthetic efficiency than the inoculated plants. Similar trends were also observed for the CCI, thus confirming that downy mildew incidence and severity, which in particular caused foliar damage at high CO2 concentrations, led to a decrease in the physiological performances.